Adverse Conditions, Psychological Aspects, and Teachers’ Tendency Toward Sustainability and a Less Conservative Future - Di Maggio, Ilaria; Ginevra, Maria Cristina; Santilli, Sara; Nota, Laura (Frontiers in Psychology, 2022)
This study aimed to examine the effect of the saliency of COVID-19, through State Anxiety and Personal Need for Structure, on teachers’ Propensity to consider the challenges of sustainable development and Propensity towards a more conservative socio-economic vision in one’s career activities. We involved a sample of 984 Italian teachers, and by manipulating saliency of COVID-19, we found that the saliency of COVID-19 positively impacted on state anxiety and, directly and indirectly through Personal Need for Structure, on propensity to consider the challenges of sustainable development in one’s career activities. Moreover, state anxiety only indirectly through Personal Need for Structure impacted on Propensity towards a more conservative socio-economic vision one's career activities.